2022
DOI: 10.3390/land11122154
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Floodplain Vegetation Response to Groundwater Variability Using the ArcSWAT Hydrological Model, MODIS NDVI Data, and Machine Learning

Abstract: This study modelled the relationships between vegetation response and available water below the soil surface using Terra’s moderate resolution imaging spectroradiometer (MODIS), Normalised Difference Vegetation Index (NDVI), and soil water content (SWC). The Soil & Water Assessment Tool (SWAT) interface known as ArcSWAT was used in ArcGIS for the groundwater analysis. The SWAT model was calibrated and validated in SWAT-CUP software using 10 years (2001–2010) of monthly streamflow data. The average Nash-Sut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…The Murrumbidgee River begins its journey from Kosciuszko National Park with an altitude of 1500 m and flows around 316 km to enter the Burrinjuck Reservoir. We have considered this Burrinjuck sub-catchment as our area of interest because of plant diversity in this floodplain due to moderate slopes in its topography, where elevation varies from 370 m to 934 m [16]. The land use and land cover in this area are mostly controlled by forest and pasture; however, wheat and cereals also grow well in this area, contributing to the national agricultural production [32].…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…The Murrumbidgee River begins its journey from Kosciuszko National Park with an altitude of 1500 m and flows around 316 km to enter the Burrinjuck Reservoir. We have considered this Burrinjuck sub-catchment as our area of interest because of plant diversity in this floodplain due to moderate slopes in its topography, where elevation varies from 370 m to 934 m [16]. The land use and land cover in this area are mostly controlled by forest and pasture; however, wheat and cereals also grow well in this area, contributing to the national agricultural production [32].…”
Section: Study Areamentioning
confidence: 99%
“…The datasets used in this study, including their source of availability, are listed in Table 1. A detailed description of SWAT input data was outlined by Muhury et al [16]. The LAI is widely used in research studies to assess the amount of leaf area in an ecosystem, which is a dimensionless and time-dependent vegetation parameter [74].…”
Section: Data Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Forested areas, characterized by high vegetation cover, decrease annual runoff because wetter forests have a stronger runoff evapotranspiration capacity. In 1909, the results of the American-led Wagon Wheel Gap experiment indicated that deforestation of 81 ha of scrub willow and coniferous forests would increase annual water yield by approximately 30 mm [12]. Wang et al (2023) [13] summarized that the driving factor for runoff changes in the upper reach of the Yellow River basin is mainly precipitation, with a contribution rate of 39.31-54.70%.…”
Section: Introductionmentioning
confidence: 99%